2020
DOI: 10.3390/nano10071342
|View full text |Cite
|
Sign up to set email alerts
|

Arrays of Plasmonic Nanostructures for Absorption Enhancement in Perovskite Thin Films

Abstract: We report optical characterization and theoretical simulation of plasmon enhanced methylammonium lead iodide (MAPbI 3 ) thin-film perovskite solar cells. Specifically, various nanohole (NH) and nanodisk (ND) arrays are fabricated on gold/MAPbI 3 interfaces. Significant absorption enhancement is observed experimentally in 75 nm and 110 nm-thick perovskite films. As a result of increased light scattering by plasmonic concentrators, the original Fabry–Pérot thin-film cavity effects are supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The embedded Au NRs enhanced PV performance by utilizing the longitudinal plasmon resonances (LPRs), which also support higher absorption and scattering cross-sectional efficiency, improving the EM field intensity significantly, especially at the wavelengths near the LPR peak (665 nm). In another study, Shen et al reported plasmon-enhanced MAPbI 3 thin-film perovskite solar cells using nanopatterned plasmonic arrays [35]. The calculated PCE of 45.5% was found in the nanopatterned plasmonic solar cell compared to its flat counterpart.…”
Section: Local Em Field Enhancementmentioning
confidence: 97%
“…The embedded Au NRs enhanced PV performance by utilizing the longitudinal plasmon resonances (LPRs), which also support higher absorption and scattering cross-sectional efficiency, improving the EM field intensity significantly, especially at the wavelengths near the LPR peak (665 nm). In another study, Shen et al reported plasmon-enhanced MAPbI 3 thin-film perovskite solar cells using nanopatterned plasmonic arrays [35]. The calculated PCE of 45.5% was found in the nanopatterned plasmonic solar cell compared to its flat counterpart.…”
Section: Local Em Field Enhancementmentioning
confidence: 97%
“…PMs such as gold (Au), silver (Ag), and copper (Cu) give rise to vivid colors due to their localized surface plasmon resonance (LSPR) [ 42 , 45 , 46 , 47 , 48 ]. The LSPR lends merit to the solar cells via light scattering and the absorbing layers [ 42 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The resulting substantial increase in light scattering can be attributed to the non-radiative decay of the PMs transferred from the light absorption layer to the main hot electron–hole pairs, which are then immediately promoted to the secondary electron–hole pair [ 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, plasmonic layers (typically 30-100 nm thick) and their associated SPRs have led to much fewer applications, albeit at the basis of the most accomplished application of plasmonics, that is, SPR biosensing. 13,14 The interest of plasmonic layers can be further enriched when drilled with nanoholes (called also nanopores or nano-apertures), either single or as a periodic array, 15,16 for applications in molecular optical sensing, 17,18 single molecule detection, 19 optical trapping, [19][20][21][22][23][24][25] DNA manipulation, 26,27 extraordinary transmission through nanohole arrays, 28,29 photovoltaics, 30 SERS, 31,32 nanochemistry, 33 and thermoplasmonics. [34][35][36] In all the plasmonic systems described above, the unavoidable heat generation in the metal due to light absorption is a natural concern.…”
Section: Introductionmentioning
confidence: 99%